Country Experiences with the Introduction and Implementation of Inflation Targeting - Otker, Inci.; Freedman, Charles (Washington, D.C. : International Monetary Fund, 2009)
This is the tenth chapter of a forthcoming monograph entitled, "On Implementing Full- Fledged Inflation-Targeting Regimes: Saying What You Do and Doing What You Say." It describes the experiences of a number of countries with the introduction and implementation of inflation targeting regimes. It discusses their motivation for introducing IT; how they fared in meeting the various conditions that some have argued are needed in advance of introducing IT; how they transitioned to a full-fledged IT framework and coordinated their preparations with other economic policies and reforms; the benefits they gained by adopting IT; the challenges they faced in implementation; and the lessons from their experiences.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet